Peran Pendidikan Sebagai Agen Perubahan Sosial: Studi Kasus di MTs. Daarul Ikhlaash Sangatta Selatan - Nur My Is Kullah; Muhammad Yasin (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
Education is a dynamic process that continuously shapes and is shaped by the changes around us. Whether in the economic, cultural, or political realms, education is the driving force for individual and societal progress. The human desire to continue to develop and adapt to the ever-changing environment is one of the main drivers in the world of education. This article aims to reveal how education, especially at MTs. Daarul Ikhlaash Sangatta Selatan, acts as an agent of social change and the role of education in reducing social and economic inequality. Through a qualitative analysis of the curriculum, learning methods, and the impact of social change on educational values ​​and policies, this study shows that the school has succeeded in integrating education with the ever-evolving social dynamics. These findings underscore the importance of education in facing the challenges of the times and building a better society.